Exploring the Acceptance of Artificial Intelligence in Healthcare in Saudi Arabia - Althubaiti, Haytham; Ali Sulaiman A. Al Yousef (Yocto Brain, 2024)
The integration of artificial intelligence (AI) into various sectors has garnered global attention, notable within the healthcare domain. In Saudi Arabia, discussions surrounding AI’s application in healthcare have been particularly pronounced, highlighted at significant gathering during the World Economic Forum in the nation’s capital. This paper aims to explore the multifaceted incorporation of AI into medical practices in Saudi Arabia, with a focus on enhancing healthcare delivery. Drawing upon insights from cultural anthropology and medicine, this study illuminates key aspects of AI adoption among Saudi medical professionals. Despite growing interest, there remains a dearth of comprehensive studies assessing AI acceptance, readiness, and proficiency among healthcare personnel, necessitating larger-scale investigations for more accurate insights. Current literature suggests that while some practitioners have embraced AI, many lack formal education and exhibit apprehension towards its utilization. Consequently, there is a pressing need for undergraduate and postgraduate educational programs tailored to AI integration within Saudi Arabia’s healthcare system. Such initiatives not only empower practitioners to harness AI’s full potential but also address concerns and apprehensions, particularly among senior professionals. By fostering a culture of AI education and proficiency, Saudi Arabia can effectively leverage AI to enhance healthcare outcomes and address emerging challenges in the medical landscape.